Tahapan Emosi dan Makna Kehilangan dalam Lirik Lagu “The Apartment We Won’t Share” - Kristi Monika; Doddy Salman (Kiwari, 2026)
The lyrics of The Apartment We Won’t Share convey a sense of loss and depict the emotional stages the character experiences through linguistic symbolism. This study applies Ferdinand de Saussure’s semiotic theory, particularly the concepts of the signifier and signified, and draws on Kübler-Ross's stages of grief. Using a qualitative descriptive method, the lyrics are analyzed as a mass communication medium that conveys emotional experiences symbolically to listeners. The analysis shows that the song represents a complex process of loss, reflecting the stages of denial, anger, bargaining, depression, and acceptance in sequence. Word symbolism, language structure, and repeated motifs in the lyrics play a crucial role in expressing the character’s emotions and psychology. The lyrics function not only as entertainment but also as a medium for communicating universal emotional experiences, providing insight into the interaction among music, psychology, and semiotics. These findings demonstrate that popular music can serve as a tool for understanding and interpreting human emotions, opening avenues for further research on the role of song lyrics in mass communication and psychological meaning-making. Lirik lagu The Apartment We Won’t Share mengandung makna kehilangan dan menampilkan tahapan emosi yang dialami tokoh melalui simbolisme bahasa. Penelitian ini menggunakan teori semiotika Ferdinand de Saussure, khususnya konsep penanda dan petanda, serta mengacu pada teori tahapan kehilangan yang dikemukakan oleh Kübler-Ross. Metode yang digunakan adalah kualitatif deskriptif dengan menganalisis lirik lagu sebagai media komunikasi massa yang menyampaikan pengalaman emosional secara simbolik kepada pendengar. Analisis menunjukkan bahwa lagu ini merepresentasikan proses kehilangan yang kompleks, mencerminkan tahapan penolakan, kemarahan, tawar-menawar, depresi, dan penerimaan secara berurutan. Simbolisme kata, struktur bahasa, dan pengulangan motif dalam lirik berperan penting dalam mengekspresikan emosi dan psikologi tokoh. Lirik ini tidak hanya berfungsi sebagai sarana hiburan, tetapi juga sebagai media untuk mengomunikasikan pengalaman emosional universal, sehingga memberikan wawasan tentang interaksi antara musik, psikologi, dan semiotika. Temuan ini memperlihatkan bahwa musik populer dapat menjadi alat untuk memahami dan menafsirkan emosi manusia, serta membuka ruang bagi studi lebih lanjut mengenai peran lirik lagu dalam komunikasi massa dan pemaknaan psikologis.